Planteamiento de una alternativa para la puesta en marcha de un sistema que permita la separación y disposición final de los cortes industriales de perforación, en el Campo Castilla de Ecopetrol S.A. (2017)
The equipment of control solids is fundamental for clean the fluid of drilling, but when it is evident losses of fluid during the process and the carvings remain with high percentages of wet at the end of treatment, this leads to cost overruns and losses of raw material. The selection of new technologies is important for to mitigate the negative effects generated for an inappropriate dehydration. The methodology of this investigation allows select equipment for a good recovery of fluid in the carvings from a parametrization of system and a simulation in Aspen Plus.